(untitled) - Jasinowski, Jerry (New York, 1995)
Analyzing the successes of fifty top companies in the steel, automobile, machine tool, computer, and other industries, a look at the comeback of American manufacturing reveals how Motorola, Xerox, Intel, Whirlpool, and others have become world-class competitors. 25,000 first printing.
Keywords: Success in business,Thành công trong kinh doanh; Case studies,Nghiên cứu tình huống; United states,Hoa Kỳ